1995
DOI: 10.1111/j.1751-1097.1995.tb02410.x
|View full text |Cite
|
Sign up to set email alerts
|

MINIMUM DOSES OF ULTRAVIOLET RADIATION REQUIRED TO INDUCE MURINE SKIN EDEMA and IMMUNOSUPPRESSION ARE DIFFERENT and DEPEND ON THE ULTRAVIOLET EMISSION SPECTRUM OF THE SOURCE*

Abstract: Many photoimmunological studies have used UV radiation sources that emit nonsolar UV spectral energy and UV doses based on nonimmunological endpoints, e.g. erythema and skin edema. Interpretation of these data has led to misunderstanding when extrapolated to hypothetical effects in humans exposed to solar UV. The purpose of this study was to: (1) establish UV dose response relationships for murine skin edema and immunosuppression, and (2) determine how different UV spectra affect these relationships. Back skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Interestingly, we found that the MED in our patient and control populations using a UVB radiation source with a kodacel filter to minimize UVC contamination was similar to those found in previous studies using unfiltered UVB radiation (18,(20)(21)(22). Several authors have postulated that the UVC component of the UVB radiation sources commonly used in phototesting studies makes a significant contribution to the erythema response (25,26,29). After minimizing UVC, we expected to see slightly higher MED values than those previously reported in SCLE populations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, we found that the MED in our patient and control populations using a UVB radiation source with a kodacel filter to minimize UVC contamination was similar to those found in previous studies using unfiltered UVB radiation (18,(20)(21)(22). Several authors have postulated that the UVC component of the UVB radiation sources commonly used in phototesting studies makes a significant contribution to the erythema response (25,26,29). After minimizing UVC, we expected to see slightly higher MED values than those previously reported in SCLE populations.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to administering physiologic doses of radiation, we also sought to define accurately the spectra of our radiation sources and to minimize contamination of our sources with heat, infrared light, and UVC radiation. Recently, several authors have argued for the routine inclusion of spectral data in every phototesting study (33,34,29). Only a few phototesting cutaneous LE studies give the percentage of UV radiation emitted from the bulbs (17,22).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the relative contribution of UVA versus UVB radiation to the modulation of traditionally studied markers of immune function, i.e. suppression of CHS sensitization, delayed hypersensitivity responsiveness and circulating immune cell numbers and function in these and other studies in humans (32)(33)(34)(35)(37)(38)(39)(40) and in animal models (41)(42)(43)(44)(45) remain quite controversial.…”
Section: Discussionmentioning
confidence: 99%
“…UVB is frequently used to induce photocarcinogenesis in animals. UVB radiation induces characteristic DNA damage on skin cells, immunosuppression, and modulation of various signal transduction pathways which can lead to cell proliferation, transformation, and cell death [6,7,8]. …”
Section: Introductionmentioning
confidence: 99%